Analysis of Business Planning and Digital Innovation in Islamic Educational Entrepreneurship for Children - Anisyah, Layin Qorin; Prabandari, Sri Palupi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to develop a business plan for Al-Fihri School to support the development of digital Islamic education services for children through a sustainable and market-oriented business strategy. Design/Methodology/Approach – This study employs a business planning approach to analyze the strategic development of Al-Fihri School. The analysis covers key business plan components, including target market identification, value proposition, marketing strategy, operational structure, and financial projections. These components are evaluated to formulate an integrated business strategy that aligns educational objectives with market opportunities. Findings – The study produces a comprehensive business plan that positions Al-Fihri School as a provider of digital Islamic education services offering interactive, personalized, and flexible learning experiences. The proposed strategy identifies appropriate target market segments, establishes a clear value proposition, formulates marketing and operational strategies, and develops financial projections to support business sustainability. The business plan demonstrates the feasibility of integrating digital technology with Islamic educational values to enhance service quality and competitiveness. Originality/Value This research provides value by examining how a business plan can guide the development of digital Islamic education services for children, offering a structured model that integrates market needs with Islamic values in a contemporary learning environment.